By the Honorable Major-General Putnam, commander of the forces of the United American States, at and near the White-Plains. A proclamation : Whereas some soldiers of the Continental Army ... have been led to desert their country's service ... Given under my hand at head-quarters, this 17th of November ... 1777 - Putnam, Israel, 1718-1790 (LLMC-digital (Series), 1777)
Offering pardons to those who had deserted from the American army and who returned to duty by January 1, 1778.